The use of legal cases as a way to enhance law students’ cognitive and communicative competences in the English classes - Arias Rodríguez, Gladis Leonor; Roberto Flórez, Eliana Edith (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This paper shows the results of a descriptive case study in language teaching, carried out in a Colombian private university. Its main aim was to encourage sixteen students from legal English 1 and 2, ninth, and tenth semesters, to analyze legal cases within the communicative approach, by motivating their cognitive competence development (making inferences, reasoning, considering different alternatives, building meanings and critical thinking). Data were gathered through researchers’ journals, an unstructured questionnaire and the students’ oral and written production. Results showed how the use of legal cases made students improve their English communication skills and their knowledge of their own field of study, which are all relevant aspects in their training as future lawyers.